Selected non-communicable diseases and risk conditions among fishermen in Divisional Secretariat Division of Kalpitiya - Harshani, S.R.A.P.; Abeysena, C. (College of Community Physicians of Sri Lanka, 2016)
Introduction: Fishermen are special group of people who are more vulnerable to non-communicable diseases due to occupation specific conditions. Objective: To determine the prevalence of accidental injuries, hypertension, malnutrition, smoking and alcohol consumption among fishermen in Divisional Secretariat Division of Kalpitiya. Methodology: This was a descriptive cross-sectional study, conducted during the period of August to October 2011. The sample consisted of 465 fishermen with ≥6 months experience in fishing and selected by applying the cluster sampling technique. The study instruments were the interviewer-administered questionnaire and the record sheet. Prevalence of the above conditions and diseases with 95% confidence intervals (CI) were calculated. Results: The prevalence of accidental injuries was 19.6%(95%CI:16%-23.2%). The prevalence of hypertension was 24.3%(95% CI:20.4%-28.2%) and it was significantly higher among those who have >10 years of service experience in the fishing sector (p<0.01) and history of smoking >10 years duration (p<0.001). The prevalence of underweight, overweight and obesity were 6.2%(95%CI:4%-8.4%), 20.6%(95%CI:16.9%-24.3%) and 2.6%(95%CI:1.2%-4%) respectively. The prevalence of current smokers and current alcohol consumers were 54.6%(95% CI: 50.2%-59%) and 60.2%(95% CI: 55.8%-64.6%) respectively. Conclusion: The prevalence of hypertension, smoking and alcohol consumption were higher and obesity was lower among fishermen than general population. Improve the knowledge on prevention and screening are recommended.
Keywords: Non-communicable diseases